The Role of Social Bricoleurs in Crafting Civil Solidarity during the COVID-19 Pandemic - Ivy Pricilia Gabriela Londa; Karina Dwita Shafira (Institute of International Studies, 2020)
The impact of the COVID 19 Pandemic has arguably been inflicted largely in the economic sector than in the health sector. People are suffering every day with millions losing jobs and fall into poverty especially in developing countries. While each government is saving the world from the global recession, the need for local lifeboat initiatives is imperative to contribute to the local economy. If not assisting the country from the severe national recession, it helps vulnerable groups and individuals to survive the global recession. The social bricoleur is a type of social enterprise characterized by its self-governing nature to venture opportunities using the readily available resources based on their tacit position in the social fabric. The research is investigating how solidarity in response to COVID-19 can be enabled by engineering ecosystem orchestration and management through social bricoleur initiatives. The study was conducted with an exploratory single case study to gain insights on how social bricoleurs play a part in addressing social gaps, using the Bagirata platform who operates in response to the COVID-19 economy as a collective effort of wealth redistribution. This middle-class society is the largest in numbers for major cities in Indonesia where the social wealth is the weakest and the population density is the highest, therefore might result in a more fractious society and prone to more social conflict. This class of society also indicates potentials for development programs, rather than the cash-transfer programs that the government has taken such measure recently. No solution fits all, the solidarity calls are inclined to create as many as solutions possible we could create with our resources.